Development of robust nuclear safeguards methods for gas centrifuge enrichment plants - Koo, Donghyeok; Seo, Junyoung; Woo, Seung Min; Kim, Byeongjun; Kim, Kyunam; Jun, Eunju; Chang, Soon Heung (Nuclear engineering and technology, 2025)
The role of nuclear energy in reducing carbon emissions has becomes increasingly significant with the intensifying climate crisis. The supply of nuclear fuels, particularly high-assay low-enriched uranium, has gained prominence with the growing demand for nuclear energy. However, the development of this technology has been challenged by proliferation risks associated with enrichment facilities. Expanding nuclear energy while securing robust nonproliferation measures is essential for maximizing the potential of nuclear energy while ensuring its peaceful application. This study proposes advanced safeguards for gas centrifuge enrichment plants for mitigating these risks and enhancing the benefits of nuclear energy. This paper introduces eight measures, including the implementation of a remote shutdown system and an off-grid power system, which are advanced safeguards that have not been utilized previously. In addition, new convergence technologies such as the instrumentation cross-verification system, digital twin real-time nuclear material control and accounting system, and remotely piloted quasi-inspection drone robot were introduced for enhancing the safeguards. Further, enhanced verification, increased sample sizes, and resident inspectors aim to rigorously enforce the existing safeguards. When implemented in a coordinated manner, these safeguard measures have the potential to enhance proliferation resistance in uranium enrichment plants while promoting their peaceful use.